Presidency as Leadership? Assessing the EU Presidency through the 2005 UK EU Presidency - Whitman, Richard G. (2006)
Presidencies play an important role in the EU and a dysfunctional Presidency has as a significant impact on its effectiveness. Although the member state holding the six-month rotating Presidency has few formal powers with which to directly influence the agenda, it is the conductor of the EU’s business and plays a key role in advancing the EU policy agenda during its term of office. The formal responsibilities of the EU Presidency are to act as chair for Heads of State and Government, ministerial and other committee and working  group meetings, to represent the Council of Ministers to the European Parliament and the European Commission and to act as EU representative vi-à-vis third countries and within international organizations.